Developing the Digital Task Analysis (DTA) framework to enable the assessment and redesign of digital resources in mathematics education - Lindenbauer, Edith; Infanger, Eva-Maria; Lavicza, Zsolt (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Digital task design is an important issue when integrating technology into mathematics education. However, existing frameworks often are not fine-grained enough for supporting teachers in designing tasks or they only focus on geometric topics. In this paper, we share a case study as the first cycle of our design-based research study that aims to extend and adapt the well-known Dynamic Geometry Task Analysis framework for analyzing further digital materials. The adapted framework is named Digital Task Analysis (DTA) model and can be utilized to analyze, modify, and design digital materials from other mathematical topics. The model focuses on supporting teachers in integrating two essential aspects within digital materials, namely creating cognitively stimulating tasks and exploiting added value of technology. In this paper, we present the first analyses of three cases representing digital materials including visualizations addressing lower secondary mathematics following the DTA model. The results show that the presented DTA model is suitable to analyze such digital materials and has the potential to support teachers in designing, assessing, and modifying digital tasks that support learners in focusing their attention on mathematically relevant aspects of digital resources, and in deepening their awareness of how to formulate targeted tasks for learners.